2011
DOI: 10.1007/s00464-011-1967-8
|View full text |Cite
|
Sign up to set email alerts
|

Radio-guided thoracoscopic surgery (RGTS) of small pulmonary nodules

Abstract: This study confirms that radio-guided localization of small pulmonary nodules is a feasible, safe, and quick procedure, with a high rate of success. The spread of the sentinel lymph node technique has increased the availability of technology required for RGTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 22 publications
1
49
1
Order By: Relevance
“…First described by Chella et al, this technique has been shown to be safe with minimal associated complications (59)(60)(61)(62). The largest series of 200 patients reported a successfully VATS resection rate of 99.5% (63). Difficulties with localization were encountered for patients with bullous emphysema who had diffusion of the radiotracer throughout the parenchyma, and with spillage of the radiotracer into the pleural space resulting in very high background counts that required a repeat procedure at a later date in a small percentage of patients (60,63).…”
Section: Discussionmentioning
confidence: 99%
“…First described by Chella et al, this technique has been shown to be safe with minimal associated complications (59)(60)(61)(62). The largest series of 200 patients reported a successfully VATS resection rate of 99.5% (63). Difficulties with localization were encountered for patients with bullous emphysema who had diffusion of the radiotracer throughout the parenchyma, and with spillage of the radiotracer into the pleural space resulting in very high background counts that required a repeat procedure at a later date in a small percentage of patients (60,63).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our report showed that VAL-MAP allowed for the resection of smaller tumors compared to other reported methods (7)(8)(9)(10)(11). This allowed for the eradication of malignant tumors by facilitating early intervention.…”
Section: Discussionmentioning
confidence: 68%
“…If a small (6). However, some papers have reported complications including pneumothorax and hemothorax requiring invasive treatment (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for pulmonary nodules with a diameter less than 1 cm, the thoracoscope becomes the unique choice for obtaining histological samples (Shan et al, 2013). It has been reported that the hook-wire positioning technique has many complications, particularly unhooking (Andrade, 2010;Ambrogi et al, 2012). In addition, partial reports have indicated that the cutting closer has cut off the steel wires during surgery (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%